Optimum Implementation Renewable Energy Systems in Remote Areas - Mozaffarilegha, Mahdi; Rashidifard, Sanaz; Mozaffarilegha, Mohammad (Iraqi Journal for Electrical and Electronic Engineering, 2020)
The growth in energy consumption and the lack of access to the electricity network in remote areas, rising fossil fuel prices, the importance of using renewable energy in these areas is increasing. The integration of these resources to provide local loads has introduced a concept called microgrid. Optimal utilization of renewable energy systems is one of their most important issues. Due to the high price of equipment such as wind turbine, solar panels and batteries, capacity sizing of the equipment is vital. In this paper, presents an algorithm based on techno-economic for assessment optimum design of a renewable energy system including photovoltaic system, batteries and wind turbine is presented.